Imperative sentence distribution on Divergent Novel - Helmanto, Fachri (CV. Mitra Palupi, 2021)
Background: Â Novel readers from Indonesia, especially students, are less able to distinguish the types of sentences.Purpose: This study aims to describe what are the kind of imperative sentences on Divergent Novel.Design and methods: The method used in this research is descriptive analysis method. The data that the researchers used as material for analysis were obtained in the novel Divergent by Veronica Roth. The procedure is as follows: 1) Selecting the data, obtained by marking parts of the text that are considered important and in accordance with the formulation of the problem; 2) Arrange the data in a systematic structure by grouping the data according to the research objectives and classifying the data into a data corpus; 3) Analyze and interpret data according to the elements studied. Based on the findings on step 2Results: This study revealed the total imperative sentence found are 106 times. The details are as followsâ€” the command category consists 41 times, the request category consists 28 times, the invitation category consists 4 times, the suggestion category consists 20 times, the advice category consists 7 times, the prohibition category consists 4 times, the compulsion category consists 2 times.